2020
DOI: 10.1038/s41392-020-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

D609 protects retinal pigmented epithelium as a potential therapy for age-related macular degeneration

Abstract: Accumulated oxidative damage may lead to irreversible retinal pigmented epithelium (RPE) cell death, which is considered to be the primary cause of dry age-related macular degeneration (AMD), leading to blindness in the elderly. However, an effective therapy for this disease is lacking. Here, we described a robust high-content screening procedure with a library of 814 protective compounds and found that D609 strongly protected RPE cells from sodium iodate (SI)-induced oxidative cell death and prolonged their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…They were in agreement with those of earlier reports indicating that PC-PLC activity is regulated in a redox-dependent manner [ 16 ] and implicate in the NADPH oxidase cascade that regulates cigarette smoke extract induce heme oxygenase-1 expression in mouse brain endothelial cells [ 24 ]. A recent study reported that in the retinal pigmented epithelium, D609 achieves its antioxidant effects primarily through elevating the expression of the metallothionein (MT) family, which is well known for its ability to eliminate oxidative risk factors [ 33 ]. In our study, the real-time measurement results of pHyPer fluorescence also show that D609 blocked insulin-generated oxidative stress in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were in agreement with those of earlier reports indicating that PC-PLC activity is regulated in a redox-dependent manner [ 16 ] and implicate in the NADPH oxidase cascade that regulates cigarette smoke extract induce heme oxygenase-1 expression in mouse brain endothelial cells [ 24 ]. A recent study reported that in the retinal pigmented epithelium, D609 achieves its antioxidant effects primarily through elevating the expression of the metallothionein (MT) family, which is well known for its ability to eliminate oxidative risk factors [ 33 ]. In our study, the real-time measurement results of pHyPer fluorescence also show that D609 blocked insulin-generated oxidative stress in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Tricyclodecan-9-yl-xanthogenate (D609) has antioxidant properties in many cell types [ 30 , 33 , 36 ] and scavenges H 2 O 2 [ 14 ]. It is also a selective competitive inhibitor of phosphatidylcholine-specific phospholipase C (PC-PLC) which breaks down phosphatidylcholine (PC) to 1, 2-diacylglycerol (DG) and phosphocholine (PCho).…”
Section: Introductionmentioning
confidence: 99%
“…The level of ROS was measured using a 2',7'-dichlorofluorescein diacetate (H2DCFDA) assay kit as described in our previous study ( 21 ). In brief, HCE cells were seeded in 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…In connection with the above, Choudhary et al, 2005 [ 313 ] reported that ARPE-19 treated with a thionein hexapeptide H-Lys-Cys-Thr-Cys-Cys-Ala-OH, which is a fragment of mouse liver MT1 [ 314 , 315 ] significantly protected against H 2 O 2 and 4-hydroxynonenal (HNE)-induced mitochondrial depolarization and ameliorated H 2 O 2 and HNE-induced apoptosis. Additional evidence about the antioxidant properties of MTs were collected in the recent work of Wang et al, 2020 [ 316 ] on ARPE-19 cells exposed to sodium iodate-induced oxidative damage. In this study, cells transfected with overexpression plasmids of MT2A and MT1G genes showed a higher cell survival rate than control cells after exposure to sodium iodate (10 ”M for 18 h).…”
Section: Metallothionein Antioxidant Systemmentioning
confidence: 99%